2012
DOI: 10.1097/sla.0b013e31825b60f0
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Early Discharge After Colorectal Surgery Due to C-Reactive Protein

Abstract: This diagnostic meta-analysis of 1832 patients--the first in the literature--provides compelling evidence that C-reactive protein on postoperative day 4 has a high negative predictive value for infectious complications of 89%. Therefore, CRP measurement allows safe and early discharge of selected patients after colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
1
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 29 publications
4
113
1
5
Order By: Relevance
“…Apart from increased morbidity and mortality rates it results in longer in-hospital stay, higher costs and even increased cancer recurrence rates [3,4]. Early diagnosis and treatment are paramount to improve these outcomes [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from increased morbidity and mortality rates it results in longer in-hospital stay, higher costs and even increased cancer recurrence rates [3,4]. Early diagnosis and treatment are paramount to improve these outcomes [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Infective complications were categorised as described elsewhere and summarised here briefly [8]. Wound (superficial surgical site) infection was defined as the presence of pus either spontaneously discharging from the wound or requiring drainage.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that the postoperative systemic inflammatory response, measure by C-reactive protein (CRP), is important in both short and long term outcomes of colorectal patients and that it may be a causal factor in development of postoperative complications [6][7][8][9][10]. A recent comprehensive review has suggested that CRP concentrations exceeding 150mg/L on postoperative days 3 to 5 should alert clinicians to the possible development of postoperative complications, including anastomotic leakage, precluding early discharge [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focus on the forecast of serious infections or leakage after intestinal surgery [19,20,21,22,23,24,25]. Some authors define the third and fourth day after surgery as a cutoff point [21,22,24]. Other authors could show no predictive value for an early diagnosis of bowel leak or inflamed disease [19,20,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…According to Riss et al [18], preoperatively increased CRP values in patients with Crohn's disease seem to be associated with a negative outcome. Most studies focus on the forecast of serious infections or leakage after intestinal surgery [19,20,21,22,23,24,25]. Some authors define the third and fourth day after surgery as a cutoff point [21,22,24].…”
Section: Discussionmentioning
confidence: 99%